Investigating DNA Methylation of Solute Carrier Genes in Colorectal Cancer: A Comprehensive Analysis Using Microarray and Bioinformatics Tools - Nur Alia Natasya Zabidi; Rashidah Baharudin; Nurul Qistina Rus Bakarurraini; Nur Alyaa Afifah Md Shahri; Francis Tieng Yew Fu; Imilia Ismail; Muhammad Redha Abdullah Zawawi; Jodi Woan-Fei Law; Learn-Han Lee; Nurul-Syakima Ab Mutalib (Progress in Microbes and Molecular Biology)
Colorectal cancer (CRC) is a major global health concern, with a significant impact on morbidity and mortality. The molecular mechanisms underlying CRC, especially DNA methylation patterns in solute carrier (SLC) genes, have gained attention due to their potential role in CRC initiation and progression. SLC genes encode transporters that play vital roles in maintaining cellular homeostasis, and alterations in their DNA methylation can influence nutrient and metabolite transport, impacting cancer cell behavior. This proposal aims to investigate the DNA methylation status of SLC genes in CRC, utilizing microarray technology and a suite of bioinformatics tools. Methods: Microarray methylation data from CRC and adjacent normal tissues underwent preprocessing, differential methylation analysis, functional enrichment exploration, and correlation analysis for a detailed study of methylation patterns. Results: This study decoded the epigenetic landscape of SLC genes in CRC, promising innovative therapeutic strategies and improved patient outcomes to combat this prevalent malignancy.